Simple handling of venous air embolism during abdominal myomectomy - Basaran,Betül (2016)
Abstract We report a case of venous air embolism during abdominal myomectomy. Although true incidence of venous air embolism is not known, in literature most of reported cases are belongs to sitting position craniotomies. Many of those are subclinical, and diagnostic methods have varying degrees of sensitivity and specificity. At time of suspicion, prevention of any subsequent air emboli is the cornerstone of treatment.